Β‐elemene increases the sensitivity of gastric cancer cells to TRAIL by promoting the formation of DISC in lipid rafts. (23rd July 2018) - Xu, Ling; Guo, Tianshu; Qu, Xiujuan; Hu, Xuejun; Zhang, Ye; Che, Xiaofang; Song, Huicong; Gong, Jing; Ma, Rui; Li, Ce; Fan, Yibo; Ma, Yanju; et al.
Abstract: β‐Elemene, an anti‐cancer drug extracted from traditional Chinese medicinal herb, showed anti‐tumor effects on gastric cancer cells. Our previous studies reported gastric cancer cells are insensitive to TRAIL. However, whether β‐elemene could enhance anti‐cancer effects of TRAIL on gastric cancer cells is unknown. In our present study, β‐elemene prevented gastric cancer cell viability in dose‐dependent manner, and when combined with TRAIL, obviously inhibited proliferation and promoted apoptosis in gastric cancer cells. Compared to β‐elemene or TRAIL alone, treatment with β‐elemene and TRAIL obviously promoted DR5 clustering as well as translocation of Caspase‐8, DR5 and FADD into lipid rafts. This led to cleavage of Caspase‐8 and the formation of death‐inducing signaling complex (DISC) in lipid rafts. The cholesterol‐sequestering agent nystatin partially reversed DR5 clustering and DISC formation, preventing apoptosis triggered by the combination of β‐elemene and TRAIL. Our results suggest that β‐elemene increases the sensitivity of gastric cancer cells to TRAIL partially by promoting the formation of DISC in lipid rafts.